2019
DOI: 10.1101/726398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex Differences in Maturation and Attrition of Adult Neurogenesis in the Hippocampus

Abstract: Sex differences exist in the regulation of adult neurogenesis in the hippocampus in response to hormones and cognitive training. Here we investigated the trajectory and maturation rate of adult-born neurons in the dentate gyrus (DG) of male and female rats. Sprague-Dawley rats were perfused one, two or three weeks after BrdU injection, marking newly dividing cells.Adult-born neurons (BrdU/NeuN-ir) matured faster in males compared to females. Males had a greater density of neural stem cells (Sox2-ir) in the dor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Choline activates the GRIN3A pathway in IDch male rats, whereas it was inhibited in ID male rat, suggesting choline could enhance activity of glutamatergic neurons to improve learning and memory function in the hippocampus. Choline supplementation may lower neurogenic potentials of neural stem cell pools via the SOX2/TCF7L2 gene network (54)(55)(56)(57), thus reducing the proliferation of neuroglia (Figure 4A). Unlike IDch males, choline supplementation did not rescue the active neuroinflammation in the ID female hippocampus, contributing to a lower expression of GRIN2A and 2B, and thus lower activity of glutamatergic system.…”
Section: Astrocyte-specific Gene Expression Changes Indicate Increase...mentioning
confidence: 99%
“…Choline activates the GRIN3A pathway in IDch male rats, whereas it was inhibited in ID male rat, suggesting choline could enhance activity of glutamatergic neurons to improve learning and memory function in the hippocampus. Choline supplementation may lower neurogenic potentials of neural stem cell pools via the SOX2/TCF7L2 gene network (54)(55)(56)(57), thus reducing the proliferation of neuroglia (Figure 4A). Unlike IDch males, choline supplementation did not rescue the active neuroinflammation in the ID female hippocampus, contributing to a lower expression of GRIN2A and 2B, and thus lower activity of glutamatergic system.…”
Section: Astrocyte-specific Gene Expression Changes Indicate Increase...mentioning
confidence: 99%
“…It is unclear how propofol might affect males and females differently, but it could potentially be related to differences in the maturation rate of new granule neurons. Death of adult-born granule cells is normally undetectable after 28 days in male rats (Dayer et al, 2003), but a recent study in adult rats showed that maturation and attrition of new cells in the DG is prolonged in females relative to males (Yagi et al, 2019). A change in the maturation time course could shift or lengthen the window of susceptibility to a propofol-induced activity decrease in new neurons in females relative to males.…”
Section: Sex Differences In Adult Neurogenesis Following Sedationmentioning
confidence: 99%